Function of 38 variants CYP2C9 polymorphism on ketamine metabolism in vitro - Xiang Zheng; Ping Fang; Su-su Bao; Dan Lin; Jian-ping Cai; Guo-xin Hu (Elsevier, 2017)
Background: Cytochrome P450 proteins (CYP 450) is the most important enzyme system of drug phase I metabolism in liver. In previous reports, reduced efficiency or increased risk of adverse events can be affected by primary sequence mutation in CYP450. Aim: To investigate the effect of gene polymorphism on the metabolism of ketamine in vitro, including the new alleles: 2C9*58, *59 and *60. Method: Incubation system which was contained insect microsome, b5, NADPH and 1M PBS incubated 10 μM-1000 μM ketamine in 37 °C for 40 min concentration of norketamine was analyzed by ultra-performance liquid chromatography-tandem mass spectrometry system (UPLC-MS/MS). Result: Catalytic activity of thirty-eight CYP2C9 alleles on ketamine metabolism to norketamine was surveyed. Compared with 2C9*1, three alleles (2C9*40, *49 and *51) was demonstrated dramatically increased intrinsic clearance (1.2-fold-3.75-fold); four subtypes (2C9*27, *31, *41 and *56) exhibited no significantly change on enzyme activity. The resting 31 alleles expressed different degrees of reduction compared with wild type. Conclusion: The result of research warns that attention should be more paid on individual who carry on the special 2C9 alleles under the situation of administrating ketamine.